Diet and orthodontics- A review - Maymona a Ibraheem; Mohammed Nahidh (College of Dentistry/ University of Baghdad, 2021)
During the course of fixed orthodontic therapy, patients should be instructed to eat specific food stuffs and beverages in order to maintain good health for the dentition and supporting structures and prevent frequent attachment debonding that prolong the treatment duration. After searching and collecting articles from 1930 till July 2021, the current review was prepared to emphasize various types of foods that should be taken during the course of fixed orthodontic therapy and to explain the effect of various food stuffs and beverages on the growth and development of craniofacial structures, tooth surfaces, root resorption, tooth movement, retention and stability after orthodontic treatment and the effect on the components of fixed orthodontic appliance.